The Influence of Social Information Processing and Perceived Usefulness in Building Customer Trust in Halodoc Users - Qhoirunnisa, Oktavia Nur; Azizah, Nurul (International Journal of Economics (IJEC), 2024)
The rapid development of digital technology has reshaped healthcare, with mobile apps such as Halodoc emerging as key tools for quick and efficient access to medical services and information. However, the success of such health apps depends on customer trust. This study investigated the relationship between social information processing (SIP) theory, perceived usefulness, and customer trust among Halodoc users in Surabaya City using quantitative methods. A total of 157 respondents were sampled, and data analysis was conducted using the SPSS application. The results showed that social information processing and perceived usefulness are simultaneously and partially significant in influencing the development of customer trust, where users assess Halodoc's information features and express satisfaction with its services, which then fosters trust. The findings highlight the importance of social information processing and perceived usefulness in building customer trust, offer insights for increasing trust in healthcare applications and inform marketing and product development strategies in the telemedicine industry.